Pengaruh Model Pembelajaran Project Based Learning Berbantuan Media Ruinmahi Terhadap Pemahaman Konsep Siswa Sekolah Dasar - Maya Miftahul Ulum; Hesti Yunitiara Rizqi; Kartika Yuni Purwanti (Universitas Pahlawan Tuanku Tambusai, 2025)
Learning strategies and innovations in teaching and learning activities are lacking, which contributes to students' lack of conceptual understanding. The purpose of this study is to ascertain how the project-based learning approach, with the aid of Ruinmahi media, affects the conceptual comprehension of third-grade elementary school pupils. This study employs a purposive sample design and a quasi-experimental research design. Tests, specifically the pretest and posttest, are used in data collection procedures. Techniques for gathering non-test data include documentation, questionnaires, unstructured interviews, and observation. Validity, reliability, difficulty, discriminatory power, normalcy, homogeneity, hypothesis testing with independent sample t-tests, and basic linear regression tests are some of the methods used to collect data. The study's findings show that the experimental class, which used the project-based learning approach with the help of ruinmah media, and the control class, which used the project-based learning model alone, had significantly different conceptual understandings. The experimental class's conceptual comprehension average is 82.36 points greater than the control class's, which is 72.36 points lower. Furthermore, with a R square value of 0.619, or 61.9%, the project-based learning paradigm with Ruinmahi's assistance has an impact on students' conceptual knowledge. This demonstrates that students' conceptual knowledge may be enhanced by 61.9% using the project-based learning methodology with the help of Ruinmahi media. The study's findings suggest that the project-based learning approach, with the use of Ruinmahi media, can enhance third-grade elementary school pupils' conceptual comprehension.